Bidirectional two-sample Mendelian randomization analysis investigates causal associations between cathepsins and inflammatory bowel disease - Wang, Na; Liu, Jun; Chai, Bao; Yao, Jianhong; Du, Xufang; Mei, Qi; Wang, Xuena (Frontiers in Genetics, 2024)
Cathepsins are key regulators of the pathology of gastrointestinal disorders such as inflammatory bowel disease (IBD), which as a kind of target protease and has attracted much attention in recent years. IBD is a chronic and relapsing inflammatory disorder of the gut. Traditional studies have shown a correlation between cathepsin and the risk of IBD, while the causal relationship remains unclear. This study utilized Mendelian randomization techniques to evaluate the causal relationships between eleven cathepsins and the subtypes of IBD, such as ulcerative colitis (UC) and Crohn's disease (CD). We also performed a series of sensitivity analyses to validate the primary Mendelian randomization (MR) results, which including Cochran’s Q test, MR PRESSO global test, and MR pleiotropy test. The forward MR analyses showed no significant association between cathepsins and IBD. Reverse Mendelian randomization analyses suggested that UC might lead to elevated cathepsin G levels [Inverse variance weighted (IVW): P = 0.038, b = 9.966], and CD might cause a decrease in cathepsin B levels [IVW: P = 0.002, b = -10.525] and cathepsin L1 levels [IVW: P = 0.045, b = -4.742]. Our findings offer novel and comprehensive evidence on the impact of UC or CD on cathepsins, potentially providing valuable insights into the treatment and prognosis of IBD.